1998
DOI: 10.1007/bf03012701
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium is the best non-depolarizing relaxant to prevent succinylcholine fasciculations and myalgia

Abstract: Rocuronium is the best non-depolarizing relaxant to prevent succinylcholine fasciculations and myalgiaPurpose: To determine which non-depolarizing relaxant among d-tubocurarine, vecuronium, atracurium, mivacurium and rocuronium prevented muscular fasciculations and myalgia following succinylcholine. Methods: In this double blind randomized study, 120 female patients scheduled for laparoscopic procedures were studied. They were divided into six groups of 20 according to the non-depolarizing pretreatment used: N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…serious side effects [1] [4] . To avoid these fasciculation related life threatening side effects caused by succinylcholine, more and more anesthesiologists have turned to use non-depolarizing muscle relaxants to facilitate intubation [5] , [6] . Many non-depolarizing muscle relaxants are currently used in clinical practice, but none of them can simultaneously satisfy the requirements of rapid onset, deep muscle relaxation, and rapid recovery for muscle relaxants to facilitate intubation as succinylcholine does [7] – [9] .…”
Section: Introductionmentioning
confidence: 99%
“…serious side effects [1] [4] . To avoid these fasciculation related life threatening side effects caused by succinylcholine, more and more anesthesiologists have turned to use non-depolarizing muscle relaxants to facilitate intubation [5] , [6] . Many non-depolarizing muscle relaxants are currently used in clinical practice, but none of them can simultaneously satisfy the requirements of rapid onset, deep muscle relaxation, and rapid recovery for muscle relaxants to facilitate intubation as succinylcholine does [7] – [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The primary search and hand search of reference lists yielded 39 articles reporting 39 studies designed as RCTs. More detailed examination found that 23 RCTs did not meet the inclusion criteria of this review, including five that used children as subjects (21–25) and 18 that failed to use intubation conditions as outcome measures (16,26–42).…”
Section: Resultsmentioning
confidence: 99%
“…Fasciculations after suxamethonium dose are common in adults but rarely observed in children. They can be prevented by small dose of rocuronium (0.06 mg·kg −1 ) injected 4 min before suxamethonium (30). Both fasciculations and muscle pain have not been regarded as a major problem in children.…”
Section: Fasciculations and Muscle Painmentioning
confidence: 99%